Targeted pricing and customer data sharing among rivals - Nicola Jentzsch; Geza Sapi; Irina Suleymanova (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
It is increasingly observable that competitors in different industries share customer data, which can be used for targeted pricing. We propose a modified Hotelling model with two-dimensional consumer heterogeneity to analyze the incentives for such sharing and its ensuing welfare effects. We show that these incentives depend on the type of customer data and on consumer heterogeneity in the strength of brand preferences. Only data on consumer transportation cost parameters is shared. The incentives to do so are stronger if consumers are relatively homogeneous. Customer data sharing is most likely to be detrimental to consumer surplus, while the effect on social welfare can be positive.
Keywords: D43; L13; L15; O30; 330; Customer Data Sharing; Price Discrimination